Impact of magmatic intrusion on diagenesis of shallow marine sandstones: An example from Qasim Formation, Northwest Saudi Arabia - Bello, Abdulwahab Muhammad; Al-Ramadan, Khalid; Koeshidayatullah, Ardiansyah I.; Amao, Abduljamiu O.; Herlambang, Adhipa; Al-Ghamdi, Faisal; Malik, Muhammad H. (Frontiers in Earth Science, 2023)
Igneous intrusions are common in sedimentary basins, and their occurrence can significantly affect the diagenesis and reservoir quality evolution of sandstones, thereby strongly impacting their hydrocarbons-, geothermal-, and CO2-storage potentials. The Qasim sandstones in the Tabuk region (NW Saudi Arabia) experienced shallow burial diagenesis (<2 km) when the Tertiary magma intruded to form basaltic sills (0.4–4 m thick). The sedimentology, tectono-stratigraphic framework, provenance, and chemostratigraphy of the Qasim Formation have been extensively covered in the literature. However, the impact of the magmatic intrusion on diagenesis and reservoir quality evolution of the sandstones remains enigmatic. This study employed thin-section petrography, QEMSCAN, XRD, SEM, and energy-dispersive spectrometer analyses to investigate the role of magmatic intrusion on diagenesis and reservoir quality of the Qasim sandstones. The results of the study indicate that reservoir porosity is principally influenced by primary depositional characteristics (grain size and sorting), diagenetic alterations, and magmatic intrusions. Sandstones with coarser grain size and better sorting have the best intergranular porosity and vice versa. The “normal” diagenetic processes that have significantly affected the reservoir porosity of the sandstones occurred during both shallow burial (eodiagenesis) and uplift (telodiagenesis). The eogenetic alterations include mechanical compaction, early diagenetic cementation by calcite, pyrite, and kaolinite, whereas the telogenetic alterations include the formation of kaolinite, goethite, hematite. Overall, mechanical compaction is the main driver for porosity loss in the sandstones. The intrusion-related diagenetic processes include the dissolution of quartz grains, rounded quartz overgrowths, and calcite cement, and the transformation of kaolinite into dickite and chlorite. Detrital quartz and rounded quartz overgrowths have undergone dissolution due to acidic pore fluids from magma and high temperature. The transformation of kaolinite into dickite occurred in a dissolution-recrystallization fashion, and the amounts of kaolinite and dickite increase in fine-grained sediments away from sill contact due to hydrodynamic processes that deposited muscovite (which form kaolinite) in low energy environments. The chloritization of kaolinite was localized, and the magma-induced dissolution of goethite likely supplied the requisite high Fe content. Additionally, the intrusion has resulted in the dissolution of the early calcite and increase in porosity towards the sill contact. However, values for compactional porosity loss have relatively remained similar both at and away from the sill contact, as the sill is too thin to exert significant vertical loading. This study has relevance to understanding hydrocarbon exploration and exploitation in sediment-lava sequences, and to understanding the development of sediment-lava systems.